The impact of the STAD model on motivating math learning in addition and subtraction - Reni Tania; Samsul Pahmi; Teofilus Ardian Hopeman; Sona Minasyan (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
The background of this study is the unsatisfactory motivation of grade II students to learn mathematics, especially in addition and subtraction lessons. The use of dull and ineffective learning techniques contributes to students' low learning motivation. Therefore, the use of STAD type cooperative learning model is one of the solutions that can be used for second grade elementary school students. This study aims to determine the effect of the STAD type cooperative learning model on grade II students' learning motivation in addition and subtraction in mathematics. The approach used is a quantitative and quasi-experimental method. The population consisted of all SDN Tugu and SDN 1 Kalaparea; the sample consisted of 35 grade II SDN Tugu students as the experimental class and 29 students of grade II SDN 1 Kalaparea as the control class. These learners were selected using a purposive sampling technique. The data collection techniques were tests, questionnaires, observation, and documentation. The techniques used to analyze the data are validity test, reliability test, normality test, homogeneity test, and T-test. Based on the results of the research that has been done, it is concluded that using the STAD type cooperative learning model increases the motivation to learn mathematics in the material of addition and subtraction of standard-length units. This can be seen from the data analysis obtained, where the sig value (2-tailed) of 0.0001 is less than 0.05, meaning that the probability value of sig.